Hepatoprotective activity of aqueous methanolic extract of Viola odorata against paracetamol-induced liver injury in mice (Bangladesh Journal of Pharmacology, 2014)
Traditionally Viola odorata is used for liver protection. To provide scientific support to its traditional use, aqueous methanolic extract of V. odorata (250 mg/kg and 500 mg/kg) was given to mice intoxicated with paracetamol. Obtained results demonstrated that the extract significantly (p